46. THE DIGITAL TRANSFORMATION REVOLUTION AND THE APPLICATION OF ARTIFICIAL INTELLIGENCE IN HEALTHCARE MANAGEMENT (Vietnam Journal of Community Medicine, 2025)
Digital transformation in the healthcare sector involves the application of information and communication technology to optimize medical examination and treatment comprehensively, bringing significant benefits to healthcare facilities and patients. This overview of the digital transformation revolution in healthcare aims to clarify the position and role of artificial intelligence applications in the management of medical examination and treatment in hospitals. It also identifies limitations, challenges, and provides recommendations and solutions for healthcare facilities in the upcoming phase.
Keywords: Digital transformation; artificial intelligence; hospital management; AI